Conceptual design of an off-shore topside CO2 injection system. (November 2017) - Zahid, Umer; Kim, Yong Heon; Ahmed, Usama; An, Jinjoo
Highlights: Process design development of an offshore CO2 injection system offering safe and improved performance. Two-stage Rankine cycle integrated with topside injection system to improve the process efficiency. Parametric analysis performed to give insight of operational parameters. Abstract: Carbon capture and storage (CCS) is one of the dominant technologies to tackle the global warming issue. The transport of CO2 for geological storage may become economically feasible by ship when the storage site location is off-shore and installment of an off-shore pipeline requires a huge capital cost. Ship transportation requires the captured CO2 to be in liquid phase under pressurized thermodynamic conditions. The injection of liquid CO2 into the geological reservoir involves pressurization and heating in order to maintain the safe well head operating conditions. This study presents two alternative top side injection process designs that can reduce the power requirement compared to the base case design. The base case design and alternative designs are simulated using Aspen HYSYS ® in order to decide the process design variables. The results show that the well head temperature of 5 °C should be maintained to avoid any hydrate formation in the injection well or at the well outlet, while, utilizing the minimum amount of energy for the injection. The study employed two-stage rankine cycle in order to extract the cold energy available from the liquid CO2 before its injection into the reservoir. The alternative designs also proposed to utilize a vapor return line in order to maintain the CO2 vessel pressure within safe limits by performing a dynamic simulation. The results show that the alternative design 1 and alternative design 2 consume almost 28% and 27.9% less power compared to that of the base case design. The specific cost per unit ton of CO2 injected for the three designs came out to be 0.75 $, 0.69 $ and 0.69 $ respectively. Finally, a sensitivity analysis has been done in order to investigate the effect of some important variables in the study.